2013
DOI: 10.1118/1.4812681
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical noise in contrast-enhanced digital mammography. Part II. Dual-energy imaging

Abstract: Image subtraction in both SE and DE CEDM reduces β by over a factor of 2, while maintaining α below that in DM. Given the equivalent α between SE and DE unprocessed CEDM images, and the smaller anatomical noise in the DE subtracted images, the DE approach may have an advantage over SE CEDM. It will be necessary to test this potential advantage in future lesion detectability experiments, which account for realistic lesion signals. The authors' results suggest that LE images could be used in place of DM images i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 54 publications
(124 reference statements)
4
59
0
Order By: Relevance
“…Table 3 shows the alpha and beta values calculated for real and simulated images. The beta value of real images used in this study (β≈3) is consistent with previously published work (Burgess 1999, Cockmartin et al 2013, Hill et al 2013. The average beta values of simulated images closely match those of real images for both 2D (<7% difference) and DBT (<4% difference).…”
Section: Real Images Synthetic Images P-value 2dsupporting
confidence: 89%
See 3 more Smart Citations
“…Table 3 shows the alpha and beta values calculated for real and simulated images. The beta value of real images used in this study (β≈3) is consistent with previously published work (Burgess 1999, Cockmartin et al 2013, Hill et al 2013. The average beta values of simulated images closely match those of real images for both 2D (<7% difference) and DBT (<4% difference).…”
Section: Real Images Synthetic Images P-value 2dsupporting
confidence: 89%
“…The anatomical structures seen in mammograms are known to be described by a power-law spectrum (Burgess 1999, Cockmartin et al 2013, Hill et al 2013, of the form shown in equation (3), where β is the power-law exponent which reflects breast tissue complexity; α is the power spectrum magnitude in units of area; and f is the spatial frequency.…”
Section: Power Spectrum Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize breast texture, radial power-law spectrum coefficients, β, estimated in LE, HE and DE recombined phantom images were compared to previously reported β values from clinical LE, HE and DE recombined CC and MLO images acquired with a prototype SenoBright® application 15 .…”
Section: Power-law Analysismentioning
confidence: 99%